Clinical Interpretation of Cardiopulmonary Exercise Testing: Current Pitfalls and Limitations - Neder, J. Alberto; Phillips, Devin B.; Marillier, Mathieu; Bernard, Anne-Catherine; Berton, Danilo C.; O’Donnell, Denis E. (Frontiers in physiology, 2021)
Several shortcomings on cardiopulmonary exercise testing (CPET) interpretation have shed a negative light on the test as a clinically useful tool. For instance, the reader should recognize patterns of dysfunction based on clusters of variables rather than relying on rigid interpretative algorithms. Correct display of key graphical data is of foremost relevance: prolixity and redundancy should be avoided. Submaximal dyspnea ratings should be plotted as a function of work rate (WR) and ventilatory demand. Increased work of breathing and/or obesity may normalize peak oxygen uptake (V̇O 2 ) despite a low peak WR. Among the determinants of V̇O 2 , only heart rate is measured during non-invasive CPET. It follows that in the absence of findings suggestive of severe impairment in O 2 delivery, the boundaries between inactivity and early cardiovascular disease are blurred in individual subjects. A preserved breathing reserve should not be viewed as evidence that “the lungs” are not limiting the subject. In this context, measurements of dynamic inspiratory capacity are key to uncover abnormalities germane to exertional dyspnea. A low end-tidal partial pressure for carbon dioxide may indicate either increased “wasted” ventilation or alveolar hyperventilation; thus, direct measurements of arterial (or arterialized) PO 2 might be warranted. Differentiating a chaotic breathing pattern from the normal breath-by-breath noise might be complex if the plotted data are not adequately smoothed. A sober recognition of these limitations, associated with an interpretation report free from technicalities and convoluted terminology, is crucial to enhance the credibility of CPET in the eyes of the practicing physician.